Modeling of parameters of pipelines of central water heating system and thermal insulation of the facade of Ukrainian buildings and facilities for different climatic conditions - Yeromin, Andriy (Technology audit and production reserves, 2017)
The object of research is the design parameters and material for the execution of the elements of the complex thermomodernization of a building or structures, namely the system of central water heating and facade thermal insulation, taking into account the impact of the climatic zones in which these facilities are operated. One of the most problematic places is not enough study and lack of justification for effective design parameters and material for the execution of pipelines of the central water heating system and facade insulation. This is necessary to significantly reduce the energy consumption of existing buildings and structures of the Ukrainian housing stock. In the course of the study, a comprehensive approach to the solution of the set tasks was used, including economic and statistical analysis, analysis of world experience and synthesis of results and retrospectives, a historical-evolutionary and logical approach. Also, system theory and system analysis were used to identify strategic prospects for a significant reduction in the energy consumption of existing Ukrainian buildings and structures. In the long term, the results are expected to be disseminated to foreign buildings and structures that have similar energy efficiency issues, including climatic zones. The effective design parameters and material for the execution of pipelines of the central water heating system have been substantiated to significantly reduce the energy consumption of existing buildings and structures of Ukrainian housing stock. The minimum thickness of the facade thermal insulation layer is determined to be 50 mm for the temperature and operating conditions under study, as well as for the characteristics of the used materials, the geometry of the pipelines and the facade thermal insulation for the first temperature zone. The resulting optimum thickness of the facade thermal insulation layer is 100 mm, and results in 100 % protection against freezing of the pipelines, even if the coolant is completely stopped for more than 24 hours after the coolant ceases to flow. The developed innovative design and design and technological solutions lead to a significant reduction in energy consumption of existing buildings and facilities of the housing stock, is operated for more than 30 years and located in different climatic zones, and helps maintain comfortable conditions for life.